Distress and adjustment among adolescents and young adults with cancer: an empirical and conceptual review - Sansom-Daly, Ursula M.; Wakefield, Claire E. (Translational Pediatrics; Vol 2, No 4 (October 16, 2013): Translational Pediatrics, 2013)
Adolescents and young adults (AYAs) with cancer must simultaneously navigate the challenges associated with their cancer experience, whilst striving to achieve a number of important developmental milestones at the cusp of adulthood. The disruption caused by their cancer experience at this critical life-stage is assumed to be responsible for significant distress among AYAs living with cancer. The quality and severity of psychological outcomes among AYAs remain poorly documented, however. This review examined the existing literature on psychological outcomes among AYAs living with cancer. All psychological outcomes (both distress and positive adjustment) were included, and AYAs were included across the cancer trajectory, ranging from newly-diagnosed patients, to long-term cancer survivors. Four key research questions were addressed. Section 1 answered the question, “What is the nature and prevalence of distress (and other psychological outcomes) among AYAs living with cancer?” and documented rates of clinical distress, as well as evidence for the trajectory of this distress over time. Section 2 examined the individual, cancer/treatment-related and socio-demographic factors that have been identified as predictors of these outcomes in this existing literature. Section 3 examined current theoretical models relevant to explaining psychological outcomes among AYAs, including developmental models, socio-cognitive and family-systems models, stress-coping frameworks, and cognitive appraisal models (including trauma and meaning making models). The mechanisms implicated in each model were discussed, as was the existing evidence for each model. Converging evidence implicating the potential role of autobiographical memory and future thinking systems in how AYAs process and integrate their cancer experience into their current sense of self and future goals are highlighted. Finally, Section 4 addressed the future of psycho-oncology in understanding and conceptualizing psychological outcomes among AYAs living with cancer, by discussing recent empirical advancements in adjacent, non-oncology fields that might improve our understanding of psychological outcomes in AYAs living with cancer. Included in these were models of memory and future thinking drawn from the broader psychology literature that identify important mechanisms involved in adjustment, as well as experimental paradigms for the study of these mechanisms within analogue, non-cancer AYA samples.